Catalyst suitable for ethylene polymerization reaction as well as preparation method and application thereof
By using a catalyst system containing a composite electron donor and inorganic oxide, the catalyst particles were prepared by spray drying, and the problem of low copolymerization performance of titanium-based catalysts was solved, and efficient copolymerization reaction between ethylene and α-olefins was achieved. The resulting polymer had high bulk density and low fine powder content.
Patent Information
- Application Number
- CN202311422466.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-30
- Publication Date
- 2025-05-02
AI Technical Summary
The existing titanium catalysts have low copolymerization performance in copolymerization of ethylene and α-olefins, which affects the density and fluidity of the polymer.
Spherical or spherical catalyst particles are prepared by spray drying by spray drying using a composite electron donor including ortho-diketone compounds/oxygenated organic matter, a mixture of magnesium halide, a titanium-containing compound and an inorganic oxide as a catalyst.
The copolymerization performance of the catalyst is improved, and the resulting polymer powder particles are uniform in shape, high bulk density and low fine powder content, which is suitable for the production of high-performance low-density polyethylene resins.
Smart Images

Figure BDA0004522219290000041 
Figure BDA0004522219290000111 
Figure BDA0004522219290000112
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of catalysts, and in particular, relates to a catalyst suitable for ethylene polymerization reaction, a preparation method and application thereof. The ethylene polymerization reaction catalyst is suitable for ethylene homopolymerization reaction and copolymerization reaction with other olefins. Background Art
[0002] Olefin polymerization catalysts are the core of olefin polymerization technology. From the perspective of the development of olefin polymerization catalysts, there are two main aspects: (1) Developing catalysts that can prepare and produce polyolefin resins with better performance or special properties; (2) On the basis of further improving catalyst performance, simplifying catalyst preparation processes, reducing catalyst synthesis costs, and developing environmentally friendly technologies. Polyethylene is currently the largest plastic variety in the world in terms of production and consumption, and is widely used in industry, agriculture, packaging and other daily life. After decades of development, catalysts suitable for ethylene polymerization can be mainly divided into chromium catalysts, vanadium catalysts, zirconium catalysts and titanium catalysts according to the metal elements used in the catalysts. Among them, titanium catalysts are the most studied type of catalyst in ethylene polymerization research due to their low price and high catalytic efficiency. The research focus of catalysts is mainly on catalyst activity, hydrogen regulation performance, copolymerization performance, particle state, particle strength and bulk density of the resulting polymer powder. Among them, excellent copolymerization performance is not only conducive to the production of high-performance ultra-low density polyethylene resin products, but also conducive to reducing the addition of comonomers when producing the same density resin grade, thereby improving the fluidity of the resin powder, ensuring stable production under high load, and reducing production costs. Therefore, improving the copolymerization performance of catalysts has important theoretical significance and important application value.
[0003] The application of supported Ziegler-Natta catalyst (ZN catalyst) in industry has been mature. Improving the traditional ZN catalyst to improve the copolymerization performance of the catalyst has important application significance and economic significance. Scientists have conducted a lot of research on improving the copolymerization performance of catalysts. Professor Czaja reported in the journal Polymer (Polymer, 2000, 41, 7899-7904) that the vanadium catalyst MgCl2(THF)2 / VCl4 / Et2AlCl was used to catalyze the copolymerization of ethylene and 1-octene. The insertion amount of 1-octene in the copolymer was 0.47%. Under the same polymerization conditions, the insertion rate of 1-octene in the copolymer obtained by using titanium catalyst was 0.39%, which was lower than that of vanadium catalyst. It shows that the active species has an important influence on the copolymerization performance of the catalyst, and the purpose of the present invention is to improve the copolymerization performance of the most widely used titanium catalyst. In addition, when ethylene and α-olefin are copolymerized, the co-catalyst alkyl aluminum also has a certain influence on the copolymerization performance of the catalyst. U.S. Patent US20120053308A1 indicates that the type of alkyl aluminum can adjust the distribution of comonomers in the polymer chain. Professor Boisson reported in ACS Catalysis (ACSCatal.2020,10,7216-7229) that the amount of cocatalyst triethylaluminum can not only regulate the kinetics of copolymerization, but also has a non-negligible effect on the distribution of comonomers in the polymer chain. It is worth noting that although the insertion of comonomers can be adjusted by the type of alkyl aluminum and the ratio with the catalyst, it is only regulated within a limited range. Improving the copolymerization performance by improving the traditional ZN catalyst is the most effective and direct way to produce new grades and high-performance products. As is known to all, in the synthesis process of ZN catalyst, the type of electron donor is crucial to the catalytic performance of the catalyst. For example, patent CN105384854A uses orthoesters as electron donors to synthesize catalysts for ethylene polymerization, which can effectively improve the bulk density of polymer powder; patents CN105111336A, CN105566524A and CN113563496A respectively use organic cyclosiloxanes, gallic acid derivatives and organosilicon polymers to improve the hydrogen regulation performance of the catalyst. The copolymerization performance of the catalyst can also be improved by selecting a suitable electron donor. Patents CN101885793A and CN101885795A respectively use composite electron donors containing organic mercaptan and organosilicon amine to improve the copolymerization performance of the catalyst, but the catalyst synthesis steps are relatively cumbersome, and the organic mercaptan and organosilicon amine used have an unpleasant odor and are expensive. Patent CN104211844A discloses a gas phase fluidized bed LLDPE catalyst and its preparation method and application.This patent adopts a one-step method to prepare LLDPE catalyst. Although this catalyst system has high activity and hydrogen sensitivity, and the polyethylene product obtained has good morphology and high bulk density; however, the titanium loading process in the catalyst synthesis step requires a large amount of titanium tetrachloride, and a large amount of toluene washing, and the catalyst particles are uneven. This not only increases the energy and material consumption of the catalyst production process, but also pollutes the environment and brings harm to production personnel. Compared with patent CN104211844A, patent CN107759716A uses asymmetric silane compounds as electron donors to synthesize catalysts suitable for gas phase polyethylene processes. The catalyst has high activity, high copolymerization, high hydrogen sensitivity, and the polyethylene product obtained has good morphology, uniform particles, and high bulk density. However, the catalyst needs to add titanium tetrachloride twice, and still requires multiple washing operations, and the synthesis of the catalyst is still somewhat cumbersome. Summary of the invention
[0004] In order to overcome the problems existing in the prior art, the present invention provides a component, preparation method and application of a catalyst for ethylene polymerization. The catalyst is suitable for ethylene polymerization and copolymerization of ethylene and α-olefins. When used for copolymerization of ethylene and α-olefins, the catalyst system has the advantages of high activity and good copolymerization performance, and the obtained polymer powder has relatively uniform particle morphology, high bulk density, and low content of fine powder in the polymer powder.
[0005] One of the purposes of the present invention is to provide a catalyst suitable for ethylene polymerization, which comprises: a composite electron donor of vicinal diketone compounds / oxygen-containing organic matter, a mixture of magnesium halide, a titanium-containing compound, an inorganic oxide and / or a reaction product.
[0006] According to the present invention, the catalyst suitable for ethylene polymerization reaction is:
[0007] The catalyst is spherical or quasi-spherical; the particle size of the catalyst is 10 to 50 microns, preferably 20 to 30 microns;
[0008] Based on the total weight of the catalyst as 100wt%, the content of titanium is 0.2-6wt%, the content of magnesium is 2.5-11.5wt%, the total amount of composite electron donor is 10-40wt%, and the content of inorganic oxide is 2-70wt%; preferably, based on the total weight of the catalyst as 100wt%, the content of titanium is 1-3.6wt%, the content of magnesium is 5-8wt%, the total amount of composite electron donor is 14.5-35wt%, and the content of inorganic oxide is 21-50wt%;
[0009] In the composite electron donor, the molar ratio of the vicinal diketone compound to the oxygen-containing organic matter is (0.01-1):1, preferably (0.05-0.5):1.
[0010] According to the present invention, the structural formula of the vicinal diketone compound is as shown in formula (I):
[0011]
[0012] In formula (I), R1 and R2 are independently selected from C1-C20 alkyl, C1-C20 halogen-containing and / or alkoxy-substituted alkyl, C6-C20 aryl, C6-C20 halogen-containing and / or alkoxy-substituted aryl, and heterocyclic group containing heteroatoms, or R1 and R2 are connected to form an aliphatic ring or an aromatic ring; specifically, the ortho-diketone compound is selected from 2,3-butanedione, 1-(4-methoxyphenyl)propane-1,2-dione, 1,2-cyclopentanedione, 2,3-pentanedione, 3-methylcyclopentane-1,2-dione, 1,2-cyclohexanedione, 3,4-hexanedione, 2,3 -hexanedione, 3,5-dimethyl-1,2-cyclopentanedione, 3,4-dimethylcyclopentenolone, 3-methylcyclohexane-1,2-dione, 5-methyl-2,3-hexanedione, 2,3-heptanedione, 1,2-indanedione, 1-phenyl-1,2-propanedione, 1-(thiophen-2-yl)propane-1,2-dione, 3,5,5-trimethylcyclohexane-1,2-dione, 1,2-naphthoquinone, 1-bromo-2,3-butanedione, 4-bromopentane-2,3-dione, 1-(3-chlorophenyl)propane-1,2-dione, 1-(4-chlorophenyl)propane-1,2-dione, furil, 1 -cyclopropyl-2-(2-fluorophenyl)ethane-1,2-dione, 4-tert-butyl-5-methoxy-o-benzoquinone, benzil, 1,2-di(pyridin-2-yl)ethane-1,2-dione, 1-(3-(trifluoromethyl)phenyl)propane-1,2-dione, 1-[4-(trifluoromethyl)phenyl]propane-1,2-dione, 3,5-di-tert-butyl-o-benzoquinone, thiophene, 4-fluorobenzil, 1,4-diphenyl-2,3-butanedione, 4,4'-dimethylbenzil, 1-(4-methoxyphenyl)-2-phenylethane-1,2-dione, 2,2-dimethyl-3,4-dihydro At least one of benzo[h]chromene-5,6-dione, 1,4-dibromo-2,3-butanedione, p-chlorobiphenyl, 4,4'-difluorobenzil, 1,2-bis(3-methylthiophene)ethane-1,2-dione, 4,4'-dimethoxyphenol ester, 3,3'-dimethoxybenzil, 1,2-bis(4-chlorophenyl)ethane-1,2-dione, and 1,2-bis(2-chlorophenyl)ethane-1,2-dione, preferably at least one of 2,3-butanedione, 1,2-bis(2-chlorophenyl)ethane-1,2-dione, 1,4-dibromo-2,3-butanedione, and 2,3-pentanedione.
[0013] According to the present invention, the oxygen-containing organic matter is selected from at least one of alcohols, phenols, ketones, aldehydes, ethers, and titanate compounds, preferably at least one of methyl formate, ethyl formate, isopropyl formate, n-propyl formate, methyl acetate, ethyl acetate, n-propyl acetate, isopropyl acetate, n-butyl acetate, isobutyl acetate, ethyl ether, propyl ether, hexyl ether, tetrahydrofuran, methyltetrahydrofuran, dimethyltetrahydrofuran, acetone, methyl isobutyl ketone, methanol, ethanol, propanol, butanol, pentanol, hexanol, 2-ethylhexanol, octanol, dodecanol, octadecyl alcohol, oleyl alcohol, benzyl alcohol, phenylethyl alcohol, cumyl alcohol, isopropyl alcohol, isopropylbenzyl alcohol, trichloromethanol, trichloroethanol, and trichlorohexanol, more preferably tetrahydrofuran.
[0014] According to the present invention, the magnesium halide is selected from at least one of magnesium fluoride, magnesium chloride, magnesium bromide and magnesium iodide, preferably magnesium chloride.
[0015] According to the present invention, the titanium-containing compound is selected from at least one of a tetravalent titanium compound and a trivalent titanium compound. Preferably, the tetravalent titanium compound has a general formula of Ti(OR): k Cl (4-k) , wherein R is a C1-C10 alkyl group, 0≤k≤4; the trivalent titanium compound is obtained by reducing a tetravalent titanium compound; specifically, the tetravalent titanium compound is selected from at least one of titanium tetrachloride, trichloromethoxytitanium, trichloroethoxytitanium, trichloro-n-butoxytitanium, dichlorodimethoxytitanium, dichlorodiethoxytitanium, dichloro-n-butoxytitanium, monochlorotrimethoxytitanium, monochlorotriethoxytitanium, monochlorotri-n-butoxytitanium, tetramethoxytitanium, tetraethoxytitanium, tetra-n-butoxytitanium, tetraisobutoxytitanium, and tetra(2-ethylhexyl)titanium, preferably titanium tetrachloride; the trivalent titanium compound is a trivalent titanium compound obtained by reducing the above-mentioned tetravalent titanium compound with metallic aluminum or with metallic magnesium, and most preferably, the product TiCl3·1 / 3AlCl3 of reducing titanium tetrachloride with metallic aluminum and / or the product TiCl3·1 / 2MgCl2 of reducing titanium tetrachloride with metallic magnesium. These titanium compounds can be used alone or in combination of two or more. These compounds may be used after being diluted with the above-mentioned organic solvents that dissolve magnesium halide.
[0016] According to the present invention, the inorganic oxide is selected from at least one of silicon oxide and aluminum oxide, preferably silicon dioxide; the particle size of the inorganic oxide is 0.01 to 8 microns, preferably 0.01 to 4 microns, and more preferably 0.1 to 1.5 microns. Silicon oxide or aluminum oxide is an inert carrier. The use of an inert carrier in spray drying helps to control the shape and composition of the catalyst particles, and the generated catalyst particles have good shape, high strength, and are not easy to break. As a preferred embodiment, no matter which inorganic oxide carrier filler (filler) is selected, it should be dry, that is, without water molecules. The filler is dried by heating for a period of time at a temperature below the sintering or melting point of the filler material (however, some fillers, such as fumed silica, naturally have a low content of residual water molecules due to their specific manufacturing methods); generally, a temperature of at least 100°C is used for drying, and lower temperatures can be used when extended drying times are acceptable or when the filler has a low melting or sintering temperature; inorganic filler materials are generally dried at a temperature of 200 to 800°C; at the same time, the filler material can be treated with one or more Lewis acids (e.g., trialkylaluminum compounds or organosilanes) in an optional amount of 1 to 10 wt% to remove polar impurities including water or hydroxyl groups in the inert carrier.
[0017] The second object of the present invention is to provide a method for preparing the catalyst suitable for ethylene polymerization reaction, comprising: reacting the components including the vicinal diketone compound, oxygen-containing organic matter, magnesium halide, titanium-containing compound, and inorganic oxide, and then spray drying to obtain the catalyst suitable for ethylene polymerization reaction. Preferably, the preparation method specifically comprises the following steps:
[0018] (1) uniformly mixing magnesium halide and oxygen-containing organic matter;
[0019] (2) adding an vicinal diketone compound, a titanium-containing compound, and an inorganic oxide, and stirring the mixture to obtain a suspension;
[0020] (3) spray drying the suspension obtained in step (2) to obtain the catalyst suitable for ethylene polymerization reaction.
[0021] According to the present invention, in the method for preparing the catalyst suitable for ethylene polymerization:
[0022] The mass ratio of the oxygen-containing organic matter to the magnesium halide is greater than 6:1, preferably (10-40):1;
[0023] The molar ratio of the vicinal diketone compound to the magnesium halide is (0.02-1):1, preferably (0.04-0.5):1;
[0024] The molar ratio of the titanium-containing compound to the magnesium halide is (0.01-1.2):1, preferably (0.1-0.4):1;
[0025] The molar ratio of the inorganic oxide to the magnesium halide is (0.4-10):1, preferably (1-5):1.
[0026] According to the present invention, in the method for preparing the catalyst suitable for ethylene polymerization:
[0027] The steps (1) and (2) are carried out under a protective gas atmosphere, for example, under nitrogen protection;
[0028] In the step (1), the mixing temperature is 0 to 90°C, and the mixing time is at least 0.1 h; preferably, the mixing temperature is 40 to 80°C, and the mixing time is 0.5 to 72 h;
[0029] In the step (2), the stirring reaction conditions are: temperature of 0 to 90° C., time of at least 0.1 h; preferably, temperature of 40 to 80° C., time of 0.5 to 72 h; in the process of preparing the catalyst suspension, the order of adding the inorganic oxide, the titanium-containing compound and the electron donor has no significant change on the catalytic performance of the final catalyst, indicating that the inorganic oxide, the titanium-containing compound and the electron donor can be added in any combination to obtain the same suspension, and then the suspension is spray-dried to obtain a spherical or quasi-spherical catalyst;
[0030] In the step (3), the spray drying conditions are: an inlet temperature of 100 to 240°C, preferably 120 to 200°C; and / or an outlet temperature of 60 to 130°C, preferably 80 to 115°C.
[0031] The third object of the present invention is to provide an application of the above-mentioned catalyst suitable for ethylene polymerization reaction or the catalyst suitable for ethylene polymerization reaction obtained by the above-mentioned preparation method in ethylene homopolymerization or copolymerization reaction.
[0032] According to the present invention, the catalyst used in the above-mentioned ethylene polymerization reaction comprises: the above-mentioned catalyst suitable for ethylene polymerization reaction or the catalyst suitable for ethylene polymerization reaction obtained by the above-mentioned preparation method, and a co-catalyst: a catalyst having the general formula of AlR a X 3-a An organoaluminum compound, wherein R is at least one of H and a C1-C18 alkyl group; X is a halogen, preferably chlorine or bromine; 0<a≤3, preferably 1<a≤3.
[0033] Among them, the molar ratio of aluminum element in the co-catalyst to titanium element in the catalyst is (1-1000):1, preferably (10-300):1; the organic aluminum compound is selected from at least one of triethylaluminum, triisobutylaluminum, tri-n-hexylaluminum, tri-n-octylaluminum, and diethylaluminum monochloride.
[0034] According to the present invention, in the ethylene polymerization catalyst, the spherical or quasi-spherical catalyst obtained by spray drying catalyzes ethylene polymerization and copolymerization of ethylene and α-olefins under the action of organic aluminum compounds. These organic aluminum compounds can be pure organic aluminum compounds or alkane or / and aromatic hydrocarbon solutions of organic aluminum compounds.
[0035] The monomers for the ethylene copolymerization reaction include ethylene and a second monomer, wherein the second monomer is selected from at least one of α-olefins having a C1 to C12 alkyl side group, and preferably, the second monomer is selected from at least one of propylene, 1-butene, 1-pentene, 1-hexene, 1-octene, and 4-methyl-1-pentene;
[0036] The temperature of the homopolymerization or copolymerization reaction is 20 to 120°C, preferably 65 to 90°C.
[0037] The catalyst of the present invention is used for ethylene polymerization and copolymerization of ethylene and alpha-olefins. The catalyst system includes two parts, a catalyst and a co-catalyst. The catalyst is prepared by dissolving magnesium halide with oxygen-containing organic matter, and adding a certain proportion of inorganic oxide carrier filler, titanium-containing compound and electron donor vicinal diketone compound to form a suspension. The obtained suspension is spray-dried and molded. The catalyst synthesis process has the advantages of simple operation and high raw material utilization rate. The catalyst particles are uniform and have few microparticles. Under the action of organic aluminum compounds, the catalyst catalyzes ethylene polymerization and copolymerization of ethylene and alpha-olefins, and has the characteristics of high catalytic activity and excellent copolymerization performance. The catalyst catalyzes the copolymerization of ethylene and alpha-olefins to obtain low-density polyethylene resin, and the obtained polymer powder has high bulk density and low fine powder content.
[0038] The spray drying method is an effective method for preparing a high-efficiency ZN catalyst suitable for ethylene polymerization. The method can prepare the various components of the catalyst into a suspension, and then obtain the catalyst through a spraying step, which greatly simplifies the synthesis process of the catalyst. The present invention selects a new type of electron donor and uses the spray drying method to prepare a catalyst suitable for ethylene polymerization. The catalyst not only has good spherical particles, but also has high polymerization activity and excellent copolymerization performance, and has the potential to produce high value-added polyethylene on existing equipment.
[0039] Other features and advantages of the present invention will be described in detail in the following detailed description. DETAILED DESCRIPTION
[0040] The present invention is described in detail below in conjunction with specific embodiments. It is necessary to point out that the following embodiments are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made to the present invention by those skilled in the art based on the contents of the present invention still fall within the scope of protection of the present invention.
[0041] The test instruments and test conditions used in the examples are as follows:
[0042] 1. Activity: expressed as the weight of resin obtained per gram of catalyst in two hours;
[0043] 2. Polymer melt index (MI): refer to ASTM D1238-99, load 2.16kg, measured at 190℃;
[0044] 3. Polymer apparent bulk density (BD): tested in accordance with ASTM D1895-69.
[0045] 4. The sieving analysis value is based on: refer to ASTM D-1921 standard.
[0046] 5. Catalyst particle size: measured by MASTERSIZER2000 particle size analyzer, termed D 10 , D 50 , D 90 It means that the special percentage distribution of the standard logarithmic particle size distribution, such as the catalyst particle size with D 50 The median particle size is 24 μm; D 10 7μm means that 10% of the particles have a diameter less than 7μm; D 90 45 μm means that 90% of the particles are smaller than 45 μm.
[0047] 6. Titanium and magnesium content: measured using Spectrumlab 752s UV-visible spectrophotometer;
[0048] 7. The content of tetrahydrofuran and electron donor in the catalyst component was determined by liquid nuclear magnetic resonance. 1 HNMR measurement and calculation.
[0049] 8. Polyethylene resin density: refer to ASTM D 1505-2010 standard.
[0050] 9. The method for testing the density of polymer powder is: density tube method.
[0051] The raw materials used in the examples and comparative examples, unless otherwise specified, are disclosed in the prior art, for example, they can be directly purchased or prepared according to the preparation methods disclosed in the prior art.
[0052] Example 1
[0053] (1) Preparation of Catalyst A
[0054] (1.1) A 250 ml four-necked flask equipped with a temperature controller, a stirrer, and a reflux condenser was purged with nitrogen and the entire system was protected by nitrogen. 4.0 g of MgCl2 and 100 ml of dehydrated tetrahydrofuran solvent were added to the four-necked flask in sequence. The mixture was stirred and dissolved at 65°C for 4 hours to obtain a clear and transparent solution. Then, 5.7 g of fumed silica gel (Cabot Corporation TS-610, with a particle size of 0.1 to 1 μm) was added and stirred for 1.5 hours to fully disperse the silica gel in the mother liquor. Then, 0.92 ml of titanium tetrachloride was added and reacted for 1.5 hours. Finally, 0.82 ml of 2,3-butanedione was added and reacted for 2 hours to obtain a slurry suspension for spraying. The mixture was kept in a nitrogen atmosphere throughout the process.
[0055] (1.2) In a closed-loop circulating airflow spray dryer (such as BüCHI Mini Spray Dryer B-290 / B-295), the suspension obtained in step (1.1) is kept at a constant temperature of 43°C, introduced into a two-fluid nozzle through a pipe using a peristaltic pump, and nitrogen with a carrier gas inlet temperature of 140°C is introduced into the spray dryer. The slurry suspension feed rate and the spray gas (N2) flow rate at room temperature are adjusted to 26 ml / min and 350 L / h, respectively, and the carrier gas (N2) flow rate is adjusted to make the outlet temperature 95°C. The powder is collected at the lower outlet of the cyclone separator to obtain spherical and quasi-spherical solid catalyst A. The particle composition of catalyst A is shown in Table 1.
[0056] (2) Ethylene slurry polymerization
[0057] 1L of hexane was added to a 2L polymerization reactor that was purged with nitrogen first and then hydrogen, and 1mL of 1M triethylaluminum hexane solution, 30mL of 1-hexene and 15mg of the solid titanium catalyst A obtained in step (1.2) were added at the same time, the temperature was raised to 85°C, hydrogen was added to 0.28MPa, and after the hydrogenation was completed, ethylene was added to 1.03MPa, and the reaction was carried out at a constant temperature and pressure of 85°C and 1.03MPa for 2 hours, then the reaction was stopped, and the temperature was lowered and the material was discharged. The polymerization results are shown in Table 2.
[0058] Example 2
[0059] The preparation process in Example 1 was followed, except that 0.41 mL of 2,3-butanedione was added at the end of step (1.1) and the mixture was reacted for 2 hours.
[0060] Example 3
[0061] The preparation process in Example 1 was followed, except that 2.3 g of 1,2-bis(2-chlorophenyl)ethane-1,2-dione was added at the end of step (1.1) and the mixture was reacted for 2 hours.
[0062] Example 4
[0063] The preparation process in Example 1 was followed, except that 2.0 g of 1,4-dibromo-2,3-butanedione was added at the end of step (1.1) and the reaction was carried out for 2 hours.
[0064] Example 5
[0065] The preparation process in Example 1 was followed, except that 1.4 mL of titanium tetrachloride was added instead of 0.92 mL of titanium tetrachloride in step (1.1).
[0066] Comparative Example 1
[0067] Compared with Example 1, the difference is that in step (1.1), 0.92 mL of titanium tetrachloride is added and reacted for 1.5 hours to obtain a slurry suspension for spraying, which is then spray-dried to obtain spherical and quasi-spherical catalysts.
[0068] Tables 1 and 2 respectively show the physical property test results and catalytic performance evaluation results of the catalyst components prepared in Examples 1 to 5 and Comparative Example 1.
[0069] Table 1. Catalyst components and particle size
[0070]
[0071] Table 2. Data of ethylene and 1-hexene copolymerization catalyzed by catalysts
[0072]
[0073] From the catalytic results in Table 2, it can be seen that although the catalysts of Examples 1 to 5 of the present invention have the same activity as the catalyst of Comparative Example 1 when catalyzing the copolymerization of ethylene and 1-hexene, and the bulk density of the obtained polyethylene powder is also the same as that of the catalyst of Comparative Example 1, both are at a higher level. However, the particle size distribution of the polymer powder obtained by the catalysts of Examples 1 to 5 is relatively concentrated, with less subdivision, and the density of the obtained polymer powder is lower when the same amount of comonomer 1-hexene is added to the polymerization system, indicating that the catalyst of the present invention has more excellent copolymerization performance and is conducive to the production of high-performance polyethylene resin with lower density.
[0074] The embodiments of the present invention have been described above, and the above description is exemplary, not exhaustive, and is not limited to the disclosed embodiments. Many modifications and changes will be apparent to those skilled in the art without departing from the scope and spirit of the described embodiments.
Claims
1. A catalyst suitable for ethylene polymerization, comprising: A mixture and / or reaction product of a composite electron donor of vicinal diketone compounds / oxygen-containing organic matter, a magnesium halide, a titanium-containing compound, and an inorganic oxide.
2. The catalyst according to claim 1, characterized in that The catalyst is spherical or quasi-spherical; and / or, The particle size of the catalyst is 10 to 50 microns, preferably 20 to 30 microns; and / or, Based on the total weight of the catalyst as 100wt%, the content of titanium is 0.2-6wt%, the content of magnesium is 2.5-11.5wt%, the total amount of composite electron donor is 10-40wt%, and the content of inorganic oxide is 2-70wt%; preferably, based on the total weight of the catalyst as 100wt%, the content of titanium is 1-3.6wt%, the content of magnesium is 5-8wt%, the total amount of composite electron donor is 14.5-35wt%, and the content of inorganic oxide is 21-50wt%; and / or, In the composite electron donor, the molar ratio of the vicinal diketone compound to the oxygen-containing organic matter is (0.01-1):1, preferably (0.05-0.5):
1.
3. The catalyst according to claim 1, characterized in that The structural formula of the vicinal diketone compound is shown in formula (I): In formula (I), R1 and R2 are independently selected from one of C1-C20 alkyl, C1-C20 halogen-containing and / or alkoxy-substituted alkyl, C6-C20 aryl, C6-C20 halogen-containing and / or alkoxy-substituted aryl, and heterocyclic group containing heteroatoms, or R1 and R2 are linked to form an aliphatic ring or an aromatic ring; and / or, The oxygen-containing organic compound is selected from at least one of alcohol, phenol, ketone, aldehyde, ether and titanate compound; and / or, The magnesium halide is selected from at least one of magnesium fluoride, magnesium chloride, magnesium bromide and magnesium iodide, preferably magnesium chloride; and / or, The titanium-containing compound is selected from at least one of a tetravalent titanium compound and a trivalent titanium compound. Preferably, the tetravalent titanium compound has a general formula of Ti(OR): k Cl (4-k) , wherein R is a C1-C10 alkyl group, 0≤k≤4; and / or, the trivalent titanium compound is obtained by reducing a tetravalent titanium compound; and / or, The inorganic oxide is selected from at least one of silicon oxide and aluminum oxide, preferably silicon dioxide; and / or, The particle size of the inorganic oxide is 0.01 to 8 microns, preferably 0.01 to 4 microns.
4. The catalyst according to claim 3, characterized in that The vicinal diketone compound is selected from 2,3-butanedione, 1-(4-methoxyphenyl)propane-1,2-dione, 1,2-cyclopentanedione, 2,3-pentanedione, 3-methylcyclopentane-1,2-dione, 1,2-cyclohexanedione, 3,4-hexanedione, 2,3-hexanedione, 3,5-dimethyl-1,2-cyclopentanedione, 3,4-dimethylcyclopentenolone, 3-methylcyclohexane-1,2-dione, 5-methyl-2,3-hexanedione, 2,3-heptanedione, 1,2-indanedione, 1-phenyl-1, 2-propanedione, 1-(thiophene-2-yl)propane-1,2-dione, 3,5,5-trimethylcyclohexane-1,2-dione, 1,2-naphthoquinone, 1-bromo-2,3-butanedione, 4-bromopentane-2,3-dione, 1-(3-chlorophenyl)propane-1,2-dione, 1-(4-chlorophenyl)propane-1,2-dione, furil, 1-cyclopropyl-2-(2-fluorophenyl)ethane-1,2-dione, 4-tert-butyl-5-methoxy-o-benzoquinone, benzil, 1,2-bis(pyridin-2-yl)ethane -1,2-dione, 1-(3-(trifluoromethyl)phenyl)propane-1,2-dione, 1-[4-(trifluoromethyl)phenyl]propane-1,2-dione, 3,5-di-tert-butyl-o-benzoquinone, thiophene, 4-fluorobenzil, 1,4-diphenyl-2,3-butanedione, 4,4'-dimethylbenzil, 1-(4-methoxyphenyl)-2-phenylethane-1,2-dione, 2,2-dimethyl-3,4-dihydrobenzo[h]chromene-5,6-dione, 1,4-dibromo-2,3-butanedione, p-chloro At least one of benzil, 4,4'-difluorobenzil, 1,2-bis(3-methylthiophene)ethane-1,2-dione, 4,4'-dimethoxyphenol ester, 3,3'-dimethoxybenzil, 1,2-bis(4-chlorophenyl)ethane-1,2-dione, 1,2-bis(2-chlorophenyl)ethane-1,2-dione, preferably at least one of 2,3-butanedione, 1,2-bis(2-chlorophenyl)ethane-1,2-dione, 1,4-dibromo-2,3-butanedione, and 2,3-pentanedione; and / or, The oxygen-containing organic matter is selected from at least one of methyl formate, ethyl formate, isopropyl formate, n-propyl formate, methyl acetate, ethyl acetate, n-propyl acetate, isopropyl acetate, n-butyl acetate, isobutyl acetate, ethyl ether, propyl ether, hexyl ether, tetrahydrofuran, methyltetrahydrofuran, dimethyltetrahydrofuran, acetone, methyl isobutyl ketone, methanol, ethanol, propanol, butanol, pentanol, hexanol, 2-ethylhexanol, octanol, dodecanol, octadecyl alcohol, oleyl alcohol, benzyl alcohol, phenylethyl alcohol, cumyl alcohol, isopropanol, isopropylbenzyl alcohol, trichloromethanol, trichloroethanol, and trichlorohexanol, preferably tetrahydrofuran; and / or, The tetravalent titanium compound is at least one selected from titanium tetrachloride, trichloromethoxytitanium, trichloroethoxytitanium, trichloro-n-butoxytitanium, dimethoxytitanium dichloride, diethoxytitanium dichloride, di-n-butoxytitanium dichloride, trimethoxytitanium monochloride, triethoxytitanium monochloride, tri-n-butoxytitanium monochloride, tetramethoxytitanium, tetraethoxytitanium, tetra-n-butoxytitanium, tetraisobutoxytitanium, tetra(2-ethylhexyloxy)titanium, preferably titanium tetrachloride; and / or, The trivalent titanium compound is a trivalent titanium compound obtained by reducing the tetravalent titanium compound with metallic aluminum or with metallic magnesium, preferably the product of reducing titanium tetrachloride with metallic aluminum, TiCl3·1 / 3AlCl3, and / or the product of reducing titanium tetrachloride with metallic magnesium, TiCl3·1 / 2MgCl2.
5. A method for preparing a catalyst suitable for ethylene polymerization according to any one of claims 1 to 4, comprising: The components including the vicinal diketone compound, oxygen-containing organic matter, magnesium halide, titanium-containing compound and inorganic oxide are reacted and then spray-dried to obtain the catalyst suitable for ethylene polymerization reaction.
6. The preparation method according to claim 5, characterized in that: The preparation method specifically comprises the following steps: (1) uniformly mixing magnesium halide and oxygen-containing organic matter; (2) adding an vicinal diketone compound, a titanium-containing compound, and an inorganic oxide, and stirring the mixture to obtain a suspension; (3) spray drying the suspension obtained in step (2) to obtain the catalyst suitable for ethylene polymerization reaction.
7. The preparation method according to claim 6, characterized in that: The mass ratio of the oxygen-containing organic matter to the magnesium halide is greater than 6:1, preferably (10-40):1; and / or, The molar ratio of the vicinal diketone compound to the magnesium halide is (0.02-1):1, preferably (0.04-0.5):1; and / or, The molar ratio of the titanium-containing compound to the magnesium halide is (0.01-1.2):1, preferably (0.1-0.4):1; and / or, The molar ratio of the inorganic oxide to the magnesium halide is (0.4-10):1, preferably (1-5):
1.
8. The preparation method according to claim 6, characterized in that: The steps (1) and (2) are carried out under a protective gas atmosphere; and / or, In the step (1), the mixing temperature is 0 to 90° C. and the mixing time is at least 0.1 h; preferably, the mixing temperature is 40 to 80° C. and the mixing time is 0.5 to 72 h; and / or, In step (2), the stirring reaction conditions are: temperature of 0 to 90° C., time of at least 0.1 h; preferably, temperature of 40 to 80° C., time of 0.5 to 72 h; and / or, In the step (3), the spray drying conditions are: an inlet temperature of 100 to 240°C, preferably 120 to 200°C; and / or an outlet temperature of 60 to 130°C, preferably 80 to 115°C.
9. Use of a catalyst suitable for ethylene polymerization as claimed in any one of claims 1 to 4 or a catalyst suitable for ethylene polymerization obtained by the preparation method as claimed in any one of claims 5 to 8 in ethylene homopolymerization or copolymerization.
10. The use according to claim 9, characterized in that: The catalyst used in the ethylene polymerization reaction comprises: the catalyst suitable for ethylene polymerization reaction, and a co-catalyst: the general formula is AlR a X 3-a An organoaluminum compound, wherein R is at least one of H and a C1-C18 alkyl group; X is a halogen, preferably chlorine or bromine; 0<a≤3, preferably 1<a≤3.
11. The use according to claim 10, characterized in that: The molar ratio of the aluminum element in the organic aluminum compound to the titanium element in the catalyst is (1-1000):1, preferably (10-300):1; and / or, The organoaluminum compound is at least one selected from triethylaluminum, triisobutylaluminum, tri-n-hexylaluminum, tri-n-octylaluminum, and diethylaluminum monochloride.
12. The use according to claim 9, characterized in that: The monomers of the ethylene copolymerization reaction include ethylene and a second monomer, wherein the second monomer is selected from at least one of α-olefins having a C1-C12 alkyl side group, preferably, the second monomer is selected from at least one of propylene, 1-butene, 1-pentene, 1-hexene, 1-octene, and 4-methyl-1-pentene; and / or, The temperature of the homopolymerization or copolymerization reaction is 20 to 120°C, preferably 65 to 90°C.
Citation Information
Patent Citations
Ethylene polymerization catalyst, preparation and application thereof
CN101885793A
Electron donor catalyst and preparation and application
CN101885795A
Gas phase fluidized bed process LLDPE catalyst, preparation and application thereof
CN104211844A
Electron donor of ethylene polymerization catalyst, ball-like catalyst and preparation method
CN105111336A
Catalyst component and catalyst for ethylene polymerization, and preparation method of catalyst component for ethylene polymerization
CN105384854A